(untitled) (Research, Society and Development, 2021)
With technological advances worldwide over the years, the use of new technologies that contribute positively to quality of life continues to be the target of much investment and studies. Nanotechnology gains prominence in this context because its use in the search for health improvement has brought good results and its use in drugs brings great contributions such as the protection to the body of drug degradation, increased solubility and bioavailability, decreased toxic effects and possible adverse reactions and a greater control and specification in the release of drugs. Brazil is the country with the largest and best infrastructure in Latin America related to nanotechnology studies with application in the health area, but with regard to production the country is at an intermediate level. The main objective of the research developed is to describe the situation of the use of nanotechnology in drugs in Brazil in the last 10 years, the advantages and disadvantages mentioned among the scientific literature and the importance and contribution of mechanisms such as this for the purpose of diagnosis and treatment of diseases. A literature review was performed, analyzing studies addressing the theme. After all the research and data collection, it was observed that nanotechnology and its use in drugs bring many benefits and help in the treatment of various diseases, but its toxic effect is still very little widespread due to the lack of clinical and pre-clinical tests and Brazil has structure and investment, but lacks incentive and professionals trained to carry out more studies and consequent productions.